(untitled) (Revista Latino-Americana de Enfermagem, 2022)
Objective: analyze the association between drug use and body dissatisfaction among adolescents in three Brazilian cities. Method: cross-sectional study, using a nested randomized controlled trial to evaluate the drug use prevention program #TamoJunto2.0 of the Ministry of Health in Brazilian schools. The sample consisted of 5,213 students from 73 schools in three Brazilian cities. The outcome body satisfaction was analyzed using the Stunkard scale and the explanatory variables were drug use and sociodemographic data. Results: the adolescents were between 12 and 14 years old; about 69.9% of them reported body dissatisfaction, and 35.67% used alcohol in the previous year. Dissatisfaction due to overweight was higher among girls (41.5%) and dissatisfaction due to underweight was higher among boys (33.1%). Adolescents who used marijuana were 39% (OR=1.39) more likely to feel dissatisfied due to underweight and being a girl increased the chances of feeling dissatisfied due to overweight by 24% (OR=1.24). Conclusion: the levels of body dissatisfaction deserve attention in hebiatric nursing care and reinforce the importance of educational strategies addressing body image and drug use, relating them to the various subjective attributes that can affect the health of adolescents, whether in the community or at school.